PDF-based parameterization for boundary layer clouds - Golaz, Jean-Christophe, author (Colorado State University. Libraries, 2001)
A new parameterization for boundary layer clouds is presented. It is designed to be flexible enough to represent a variety of cloudiness regimes without the need for case-specific adjustments. The methodology behind the parameterization is the so-called assumed PDF method. The parameterization differs from traditional higher-order closure or mass-flux schemes in that it achieves closure by the use of a relatively sophisticated joint probability density function (PDF) of vertical velocity, temperature, and moisture. Because predicting the full subgrid-scale PDF is not feasible, a family of PDFs that is flexible enough to represent various cloudiness regimes is identified and used. The methodology is as follows. Predictive equations for grid box means and a number of higher-order turbulent moments are advanced in time. These moments are in turn used to select a particular member from the family of PDFs, for each time step and grid box. Once a PDF member has been selected, the scheme integrates over the PDF to close higher-order moments, buoyancy terms, and diagnose cloud fraction and liquid water. Since all these are derived from a unique joint PDF, they are guaranteed to be consistent with one another. Results from simulations of five different cases with the new parameterization are presented and contrasted with data simulated by large-eddy simulation (LES). The cases include a clear convective layer, trade-wind cumulus, cumulus clouds over land, marine stratocumulus and an intermediate and challenging regime of cumulus rising into stratocumulus. The cloud cover in the cloudy cases varied widely, ranging from a few per cent cloud cover to nearly overcast. In each of the cloudy cases, the parameterization predicted cloud fractions that agree reasonably well with the LES. Typically, cloud fraction values tended to be somewhat smaller in the parameterization, and cloud base and top heights were slightly underestimated. Liquid water content was generally within 40% of the LES predicted values for a range of values spanning almost two orders of magnitude. This was accomplished without the use of any case-specific adjustments.
December 18, 2001.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 2002.
Keywords: Clouds -- Mathematical models; Boundary layer (Meteorology) -- Mathematical models